A Psalter from Tübingen: Although Inconspicuous the Text, Neverthless a Treasure for Manuscriptology - Six, Veronika (Aethiopica, 2010)
The University Library of Tübingen, Germany, has acquired a manuscript with the text of a Mäzmurä Dawit. The manuscript is dated. At first glance it seems to be the standard Psalter. But there are several criteria, which give insight into the manuscript culture, and which has not changed during centuries. The modern printed editions of a Mäzmurä Dawit exactly follow the scheme of the long tradition. Besides being a perfect witness to the traditional manuscript culture and individual use of a Mäzmurä Dawit, the Tübingen manuscript contains elements, which open the window to different aspects, as for example, worship and belief, iconography, or history.